2018
DOI: 10.5194/acp-18-4217-2018
|View full text |Cite
|
Sign up to set email alerts
|

The role of the winter residual circulation in the summer mesopause regions in WACCM

Abstract: Abstract. High winter planetary wave activity warms the summer polar mesopause via a link between the two hemispheres. Complex wave-mean-flow interactions take place on a global scale, involving sharpening and weakening of the summer zonal flow. Changes in the wind shear occasionally generate flow instabilities. Additionally, an altering zonal wind modifies the breaking of vertically propagating gravity waves. A crucial component for changes in the summer zonal flow is the equatorial temperature, as it modifie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…First, a control (CTL) simulation was carried out where both the sub-grid scale orography (SSO) scheme and non-orographic GW scheme are used and two sensitivity tests where (a) the SSO scheme was disabled (no-SSO, hereafter) and (b) the non-orographic GW scheme was disabled (no-GWD, hereafter). Although the exclusion of GW drags results in a very strong forcing, this kind of simulation has been performed previously using other models (e.g., EMAC (Eichinger et al (2020)), WACCM (Kuilman & Karlsson, 2018) and CMAM (Ren et al, 2011)) and has been shown to be useful in understanding the importance of GW drags for middle atmospheric dynamics. In ICON, the SSO drag is treated after Lott and Miller (1997), and the non-orographic GW drag parameterization that treats the generation, propagation, and breaking of GWs from synoptic-scale flow (e.g., fronts, convection, jet streams) is based on the works of Warner and McIntyre (1996) and Scinocca (2003).…”
Section: Ua-icon Setup and Simulationsmentioning
confidence: 99%
“…First, a control (CTL) simulation was carried out where both the sub-grid scale orography (SSO) scheme and non-orographic GW scheme are used and two sensitivity tests where (a) the SSO scheme was disabled (no-SSO, hereafter) and (b) the non-orographic GW scheme was disabled (no-GWD, hereafter). Although the exclusion of GW drags results in a very strong forcing, this kind of simulation has been performed previously using other models (e.g., EMAC (Eichinger et al (2020)), WACCM (Kuilman & Karlsson, 2018) and CMAM (Ren et al, 2011)) and has been shown to be useful in understanding the importance of GW drags for middle atmospheric dynamics. In ICON, the SSO drag is treated after Lott and Miller (1997), and the non-orographic GW drag parameterization that treats the generation, propagation, and breaking of GWs from synoptic-scale flow (e.g., fronts, convection, jet streams) is based on the works of Warner and McIntyre (1996) and Scinocca (2003).…”
Section: Ua-icon Setup and Simulationsmentioning
confidence: 99%